Learning Video Making Workshop: Computer-Based Learning in the Industrial Revolution 4.5 Era at PGRI Sodonghilir Tasikmalaya - Rahadian, Dian; Dadang, Dadang; Nurhayati, Fitri; Hidayat, Andi; Fatimah, Imas; Mariah, Dede; Febriyanti, Fitri Ayu; Kusnadi, Engkus; Lani, Lani (Fakultas Kewirausahaan Universitas Garut, 2023)
Along with technological advancements, traditional learning faces challenges. In today's digital era, conventional learning, which relies solely on lectures, is no longer sufficient to motivate students. The community service approach used in the